Effectiveness of regular physical activity on exercise tolerance and biochemical parameters in high-risk prostate cancer patients during radiotherapy - Hojan, Katarzyna; Ozga-Majchrzak, Owidia; Górecki, Maciej; Leporowska, Ewa; Milecki, Piotr (Journal of Medical Science, 2015)
Introduction. Radiotherapy (RT) is an important modality for curative treatment in high-risk prostate cancer (PCa) patients that improves overall survival, however, it may cause unfavorable changes in physical fitness, increased risk factors for cardiovascular and metabolic complications. The effects of physical exercise on aerobic capacity and on serum levels of liver and renal function indices in PCa patients undergoing RT are still unknown. Aim. The purpose was to assess the impact of supervised physical activity on aerobic capacity, hemorheology and metabolic biomarker levels in high-risk PCa patients during RT. Material and methods. Seventy-two men were randomly allocated to two groups before RT for high-risk prostate carcinoma. Thirty-six men conducted physical exercise (EG) and the other 36 men were a control group (UC). Outcomes measured were 6-Minute Walk Test (6MWT), blood parameters, serum levels of hepatic and renal function biomarkers (urea, creatinine, alanine and aspartate aminotransferase, PSA) in a modified shuttle test before and after RT. Results. After RT, decreased diastolic blood pressure (before test p = 0.05) was observed in the EG and in the UG, there was an increase in resting heart rate (p = 0.017), a decrease in walking distance (p = 0.036), and an increase in Borg fatigue score during the 6MWT. There was no statistically significant change in renal biomarkers or PSA in the liver in either group. Conclusions. Physical activity in prostate carcinoma patients during RT improves capacity tolerance with a decrease in Borg fatigue score, but this activity did not influence on serology outcomes or other blood indicators during RT